The Game of Manners : Japanese Art in 1990. (Mito : Art Tower Mito - Contemporary Art Gallery, 1990)
Kamiyama, Akira ; Sekiguchi, Atsuhito ; Ara, Atsuko ; Senzaki, Chieo ; Hirabayashi, Kaoru ; Ueno, Keiichi ; Kawashima, Keiju ; Nakahara, Kohdai ; Hashimoto, Masayuki ; Sakaguchi, Masayuki ; Yano, Michiko ; Yoshizawa, Mika ; Fukuda, Miran ; Aoki, Noe ; Masuda, Satoko ; Toya, Shigeo ; Nishina, Shigeru ; Ohtake, Shinroh ; Kawamata, Tadashi ; Kuniyasu, Takamasa ; Miyajima, Tatsuo ; Akiyama, Yoh ; Nishimura, Yohei
2 ex.: 1 ex. (vol. 1) in Japans (met ill.) en 1 ex. in Engels (zonder ill.)
The Game of Manners : Japanese Art in 1990, Art Tower Mito - Contemporary Art Gallery, Mito, Period: March 22 - may 6, 1990 ; Period: May 19 - July 1, 1990
Engels & Japans
kunstcatalogus
Keywords: Japan